2008
DOI: 10.1186/bcr2143
|View full text |Cite
|
Sign up to set email alerts
|

ERalpha-status of disseminated tumour cells in bone marrow of primary breast cancer patients

Abstract: Introduction Isolated disseminated tumour cells (DTC) are regarded as surrogate markers for minimal residual disease in breast cancer. Characterisation of these cells could help understand the known limitations of adjuvant therapy. Of particular interest is their oestrogen-receptor (ER) status because endocrine adjuvant therapy remains a cornerstone of breast cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 34 publications
4
77
0
1
Order By: Relevance
“…Although chemotherapy targets highly proliferative cells, dormant tumor cells are mostly either slowly proliferating or in a state of arrested growth. In patients with ER-positive primary tumors with tumor cell spread into their bone marrow, only 14% had ER-positive disseminated tumor cells [26]. This lower ER positivity may cause a low response to endocrine therapy in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although chemotherapy targets highly proliferative cells, dormant tumor cells are mostly either slowly proliferating or in a state of arrested growth. In patients with ER-positive primary tumors with tumor cell spread into their bone marrow, only 14% had ER-positive disseminated tumor cells [26]. This lower ER positivity may cause a low response to endocrine therapy in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 88 patients with ER-positive primary tumors who presented with DTC in their bone marrow, only 14% had ER-positive DTC. 65 The loss of ER-positivity in DTC or CTC may explain the failure of endocrine therapy in a subset of ER-positive patients. Therefore, determining the phenotype of MRD is becoming increasingly important, as DTC and CTC are the targets of all adjuvant therapies.…”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…We and others previously reported a discrepancy between cancer cells from the primary tumor and those in secondary sites, such as blood and bone marrow, especially with regard to HER2 and ER status. 15,[62][63][64][65] HER2 gene amplification can be acquired during disease progression, even if the primary tumor was HER2-negative at the beginning of treatment. 66 However, patients with HER2-negative tumors but HER2-positive MRD are not eligible for HER2-based treatment.…”
Section: Targeting Signal Transductionmentioning
confidence: 99%
“…Repeated invasive biopsies are unacceptable. There is considerable evidence that CTCs/DTCs (2,3,(8)(9)(10) are an effective means for following genetic changes that accompany cancer progression. Our previous studies (11,12) showed that protein expression levels and gene amplification of HER2 could change throughout disease progression and HER2 and uPAR overexpression and gene amplification are correlated by analysis of gene status and expression in CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies we subjectively quantified gene expression levels of individual CTCs into 1-3 categories after immunofluorescence (IF) staining. In other studies IF staining or/and immunohistochemistry (8,10,13) was used for evaluating positivity for HER2, oestrogen-receptor (ER) or other tumor markers. HER2 testing in CTCs may have clinical relevance for HER2-targeted therapy as HER2-positive CTCs and DTCs can be detected in patients with HER2-negative primary tumors who currently do not have access to HER2-targeted therapy (e.g.…”
Section: Introductionmentioning
confidence: 99%